Peningkatan Keterampilan Menulis Huruf Tegak Bersambung Melalui Penerapan Metode Struktural Analitik Sintetik Pada Siswa di Kabupaten Barru - Syamsuriani, Syamsuriani; Marda, Andi Besse (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2023)
Abstract Synthetic Analytic Structural Model (SAS) is a method of analysis methods such as sentence methods and word methods that prioritize meaning, which consists of forms, arrangements and structures that have meaning rather than the number of elements. The technique of implementing the SAS (Synthetic Analytics Structure) method is the skill of choosing letter cards, word cards, and word cards arranged into sentences. The approach used in this study uses a qualitative approach, with a type of classroom action research. In general, class action research (PTK) consists of several cycles or repetitions of cycles. Each cycle consists of four steps, namely: (1) planning; (2) implementation, (3) observation/observation; and (4) reflection. This research was conducted at SD Inpres Mattirowalie, Barru Regency with a total of 120 people. The sample of this study was 20 grade I students of SD Inpres Mattirowalie Kec. Barru for the 2020/2021 school year, consisting of 11 male students, and 9 female students. The population of this study is reachable so that the authors use a total sample (sample population). The data sources of this study are students, teachers, and principals. Research Work Procedures This class action research is carried out in two cycles of activity, with the following details;1) Cycle I is carried out as many as two meetings (6 class hours). 2) cycle II is held twice (6 hours of lessons). The data obtained are analyzed using quantitative and qualitative analysis. Data collection techniques are carried out with documentation techniques, observation techniques, and test techniques. Based on the results of research that has been carried out, it can be seen that there is an increase in students' skills in writing continuous upright letters using the Synthetic Analytical Structural Method. This can be seen from the pre-cycle results before applying the Synthetic Analytical Structural method where only 4 students or 30% of students meet the Maximum Completion Criteria (KKM), while the other 16 students or (70%) students have not met (KKM). The increase in cycle I shows that students achieve the Classical completion criteria, namely as many as 11 students or 55% of students have reached KKM while in cycle II the Classical Completion Criteria are 17 students (85%). Thus the learning outcomes obtained by students are said to be successful if 80% of the total number of students has reached KKM.